2019
DOI: 10.1002/zamm.201800240
|View full text |Cite
|
Sign up to set email alerts
|

Closed‐form solutions for a circular inhomogeneity in nonlinearly coupled thermoelectric materials

Abstract: Thermoelectricity is a class of material possessing the ability of interconverting heat and electricity. For the sake of high conversion efficiency, inclusions/fibers are usually introduced into thermoelectric materials. However, the discontinuity of material property and geometry brought by inclusions/fibers might result in severe stress concentration and thus greatly affect the mechanical properties of thermoelectric material in its engineering service. This paper introduces a nonlinear coupled thermal–elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 33 publications
(87 reference statements)
0
9
0
Order By: Relevance
“…In a Cartesian coordinate system {𝑥 𝑖 } (𝑖 = 1, 2, 3), let H, T, 𝐉 and 𝐉 𝑢 be, respectively, the thermoelectric potential, temperature, electric current density vector and energy flux vector in a homogeneous and isotropic nonlinearly coupled thermoelectric material. The constitutive equations and equilibrium equations are [17][18][19][20]…”
Section: Complex Variable Formulationmentioning
confidence: 99%
“…In a Cartesian coordinate system {𝑥 𝑖 } (𝑖 = 1, 2, 3), let H, T, 𝐉 and 𝐉 𝑢 be, respectively, the thermoelectric potential, temperature, electric current density vector and energy flux vector in a homogeneous and isotropic nonlinearly coupled thermoelectric material. The constitutive equations and equilibrium equations are [17][18][19][20]…”
Section: Complex Variable Formulationmentioning
confidence: 99%
“…For the two-dimensional problem of nonlinearly coupled transports of heat and electricity in a homogeneous and isotropic thermoelectric material, the thermoelectric field characterizing the thermoelectric potential, the electric current density, the temperature, and the energy flux can be expressed in terms of two analytic functions f (z) and g(z) of the complex variable z = x 1 + ix 2 as follows [5,[7][8][9] :…”
Section: Complex Variable Formulationmentioning
confidence: 99%
“…Thermoelectric materials have been found increasing applications in the fields of energy production, conversion, conservation, and nondestructive testing (NDT) due to their inherent property of coupled transports of heat and electricity [1][2][3] . In recent years, the effects of nonlinear thermoelectric coupling on the electro-thermo-mechanical responses of thermoelectric materials have been investigated by several authors [4][5][6][7][8][9][10][11][12][13] . However, certain important issues arising in the discussion of nonlinear thermoelectric materials remain unresolved.…”
Section: Introductionmentioning
confidence: 99%
“…It is found that the results of the temperature field presented in Figure 2 agree well with those obtained in refs. [21, 25]. Figure 2a shows that the maximum temperature difference in the matrix around the interface increases along with the increase of the thermal resistance.…”
Section: Numerical Examplesmentioning
confidence: 99%
“…As the von Mises fracture criterion is commonly used in semiconductors, we also analyze the effect of the external energy flux on the von Mises stress in the matrix around the interface. The von Mises stress σs is defined by [25] σs=σxσy2+σxσz2+σzσy2+6σxy22…”
Section: Numerical Examplesmentioning
confidence: 99%